PELAKSANAAN RENCANA TATA BANGUNAN DAN LINGKUNGAN KAWASAN KOTA LAMA SEMARANG - Ardian Jati; Wiwik Widayati; Puji Astuti (Journal of Politic and Government Studies, 2015)
City of Semarang, has a valuable asset in the form of the Old City, which is a visual image of the splendor of European architecture in the past. The existence of the building and the old building by the Dutch in the Old Town area to be conserved and managed by the Government as stipulated in Law No.11 of 2010 on Heritage and Building Management Plan and Environmental ( RTBL ). The method used in this study is a qualitative research, research that is empirical ( observable by the senses correspond to reality ). Qualitative research emphasizes the process and meaning rather than quantity, frequency or intensity ( which is mathematically measurable ). This study shows that mplementation of the Building Management Plan and Environmental Old Town area is not optimal, because it can not achieve the goal to make the Old Town as an area of cultural tourism that preserve historical values. improvements need to be done, especially in terms of communication, resources, disposition and bureaucratic structure for the implementation of the policy to be more optimal.